Ketidakberdayaan dan Perilaku Bunuh Diri: Meta-Analisis - Tience Debora Valentina; Avin Fadilla Helmi (Faculty of Psychology Universitas Gadjah Mada, 2016)
The incidence of suicide increases in Indonesia and around the world that encourage the growing of research on suicidal behavior. Hopelessness recognized as a strongly predictor of suicidal behavior, including suicidal ideas and suicide attempts (Beck, Brown, Berchick, Stewart, & Steer, 1990; Reinecke and Franklin-Scott, 2005). However, the empirical results show the correlation between hopelessness and suicidal behavior seem to be less consistent. The purpose of this study is to determine the relationship of hopelessness and s uicidal behavior through the study of meta-analysis. There are 27 studies are including in this meta-analysis study. Two artifacts allow for correction in these study are sampling error and measurement error. The result shows that the correlation of hopele ssness and suicidal behavior is 0.360, with the confidence level is 95%